Improving outcomes of type 2 diabetes mellitus patients in primary care with Chronic Care Model: A narrative review - Arwa Ahmed Al‐Qahtani (Journal of General and Family Medicine, 2024)
Abstract Designed and implemented over two decades ago, the Chronic Care Model is a well‐established chronic disease management framework that has steered several healthcare systems in successfully improving the clinical outcomes of patients with type 2 diabetes mellitus. Research evidence cements the role of the Chronic Care Model (with its six key elements of organization of healthcare delivery system, self‐management support, decision support, delivery system design, clinical information systems, and community resources and policies) as an integrated framework to revamp the type 2 diabetes mellitus‐related clinical practice and care that betters the patient care and clinical outcomes. The current review is an evidence‐lit summary of importance of use of Chronic Care Model in primary care and their impact on clinical outcomes for patients afflicted with one of the most debilitating metabolic diseases, type 2 diabetes mellitus.